Emissões de gases de efeito estufa e composição da matéria orgânica em uma lagoa costeira, urbana no Rio de Janeiro, Brasil - Viana, Alessandra da Fonseca (2019)
Present greenhouse gas concentrations in the atmosphere have reached alarming levels and in 2019, CO2 and CH4 concentrations have reached 410,6±0,1 ppm and 1866,1 ppb, respectively. Therefore, the objective of this study is to understand the dynamic of the greenhouse gases in an urban, coastal lagoon and to evaluate the origin of organic matter. The collections took place in Rodrigo de Freitas Lagoon, in four periods in 2016 and found a mean diffusive flux of -1,466.8 mgCO2.m-2 d -1 , 113.7 mg.CH4m-2 d -1 and 1.97 mgN2O.m-2 d -1 . In relation to bubbling fluxes, the mean values were 5.01 mgCO2.m-2 d -1 and 58.28 mgCH4.m-2 d -1 . The concentrations of n-alkanes varied between 2.43 and 25.82 µg.g-1 and C29 was predominant compound in most sites, Indicating the importance terrestrial compounds, but also with important petrogenic source. The total concentration of sterols ranged from 2.76 to 56.01 µg.g-1 , while β-sitostanol was the most abundant compound, indicating the importance of phytosterois and coprostanol was the most relevant compound at the sites under influence of domestic effluents. We conclude that, during the analyzed period, the region is a sink of carbon dioxide and a source of methane and nitrous oxide. The organic matter mainly originated from terrestrial plants, petroleum derivatives and domestic sewage, that reaches the lagoon by the rivers and irregular galleries is source of eutrophication producing high concentrations of gases in its sediments and generating emissions to the atmosphere.